2020
DOI: 10.1039/c9an01546a
|View full text |Cite
|
Sign up to set email alerts
|

Versatile printed microheaters to enable low-power thermal control in paper diagnostics

Abstract: Reusable, low-power, low-cost, printed microheaters developed for practical use in in-field and point-of-care diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The thermal convection loss integrated into the lab-on-chip fabricated device can be reduced, with an analysis of the contact resistance between the pads and the cables of the attached sensors and a better understanding on the heat transfer process. For instance, Jiang [ 12 ], Byers [ 21 ], and Tiwari [ 22 ] used a time response of the temperature for a specified provided voltage, which can be very useful to describe the transient thermal analysis [ 3 ]. In the work of Jiang [ 12 ], this temporal curve characterization with hysteresis was developed, showing the fluid heating response for a provided pulsating power between 0.2 W and 3.2 W, and a flow rate of 4 mL/min, demonstrating the rapid heat transfer process when a liquid flow is applied, which, although not considered in that work, provides a key characteristic for use in microsystem flow sensors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermal convection loss integrated into the lab-on-chip fabricated device can be reduced, with an analysis of the contact resistance between the pads and the cables of the attached sensors and a better understanding on the heat transfer process. For instance, Jiang [ 12 ], Byers [ 21 ], and Tiwari [ 22 ] used a time response of the temperature for a specified provided voltage, which can be very useful to describe the transient thermal analysis [ 3 ]. In the work of Jiang [ 12 ], this temporal curve characterization with hysteresis was developed, showing the fluid heating response for a provided pulsating power between 0.2 W and 3.2 W, and a flow rate of 4 mL/min, demonstrating the rapid heat transfer process when a liquid flow is applied, which, although not considered in that work, provides a key characteristic for use in microsystem flow sensors.…”
Section: Discussionmentioning
confidence: 99%
“…The common theoretical resistance calculated in this work was less than the practical resistance measured with respect to the heater, which is related to the effects of resistivity on thin films that should be considered with a different model. In the model presented by Byers [ 21 ], a resistor performance analysis in terms of response time was used, which can be advantageous. An appropriate model can be used for materials that are reduced to dimensions on the nanoscale, in which many of the common properties or characteristics are no longer valid; likewise, it has been shown that the mechanical, thermodynamic, electrical, and optical properties are altered due to size differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Byers and colleagues reported the development and application of resistive microheaters printed with nanosilver ink for improved heating in paper POC and in-field diagnostics. 285 They pointed out the predictability and versatility of resistive heating and demonstrated both isothermal nucleic acid amplification at 65 °C and 16-hour bacterial culture at 37 °C using their microheaters and low-power battery heating. The heaters cost between US $0.17 and $0.58, are reusable and stable over 6 months, and can be wetted without degradation or reduction in conductivity.…”
Section: Reduce Power Dependencementioning
confidence: 99%
“…[ 25 ] Other methods are spray coating of Ag nanowire/carbon nanotube composites [ 26 ] or patterned casting of Ag on flexible polymer foil . [ 27 ] Such printed flexible heaters find their application in wearable thermotherapy pads, [ 28 ] paper diagnostics, [ 29 ] and other wearable applications. [ 30 ] Moreover, only a few publications can be found in the field of inkjet printed heaters such as Byers et al with silver microheaters, [ 29 ] Wang et al with silver nanowire flexible transparent heaters, [ 31 ] or Huang et al with silver nanowires for stretchable heaters.…”
Section: Introductionmentioning
confidence: 99%